SISTEM PAKAR TALENTA IMPLEMENTASI KECERDASAN BUATAN DALAM PELAYANAN PUBLIK MENUJU SRAGEN SMART CITY - Imas Wulandari (Badan Perencanaan Pembangunan Daerah, Penelitian dan Pengembangan Kabupaten Sragen, 2018)
In the context of developing Sragen Regency towards a smart city, the use of information technology has begun to be developed towards the application of artificial intelligence (AI). The TALENTA expert system (Complete Question Regarding Public Services and Licensing) can start as an AI application in the field of government, especially in the field of public services. As an effort to improve the quality of public services, ASN (Civil Servant) is needed which has capability in carrying out its duties, besides being able to provide training for ASN to become more experienced like an expert in the field of public services and licensing, as well as to improve public understanding. With increasing public understanding, regarding definite and transparent information about requirements, procedures, completion time and costs in managing public services and licensing, the public's assessment of the government as a public service provider is getting better. It is expected that the TALENTA Expert System is able to accelerate the direction and strategy of implementing ICT in order to achieve the goals and objectives of the 2016-2021 RPJMD of Sragen Regency in the 1st Mission, namely to realize a clean and accountable government through improving effective, aspirational, participatory and transparent governance with the aim improve the quality of public services and the goal of increasing the quality and quantity of information technology-based governance (ICT).